USING TRADITIONAL AND INNOVATIVE METHODS OF FOLKLORE IN THE EDUCATIONAL PROCESS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores the role of folklore in the educational process by analyzing both traditional and innovative methods of its implementation. Folklore, as a reflection of national identity and cultural heritage, remains an essential tool in the development of moral, aesthetic, and linguistic competence among students.